Film journalist and historian Rafique Baghdadi - Mumbai Archive Project (Jio Institute, 2024)
Mr Rafique Baghdadi is a long-time resident of Mazagaon and an expert on the culture and heritage of his neighbourhood. He is a veteran film journalist by profession and often visits the kudd with fellow heritage enthusiasts to give them an introduction to the multicultural history of Mazagaon.